1999
DOI: 10.1034/j.1399-3003.1999.14a05.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased airway responsiveness to acetaldehyde in asthmatic subjects with alcohol-induced bronchoconstriction

Abstract: Increased airway responsiveness to acetaldehyde in asthmatic subjects with alcoholinduced bronchoconstriction. M. Fujimura, S. Myou, Y. Kamio, Y. Ishiura, K. Iwasa, T. Hashimoto, T. Matsuda. #ERS Journal Ltd 1999. ABSTRACT: Bronchial responsiveness to acetaldehyde, a main factor in alcoholinduced bronchoconstriction, and methacholine were compared between 10 subjects with alcohol-induced bronchoconstriction and 16 asthmatic subjects without alcohol sensitivity.In the alcohol-sensitive group, the geometric mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Although a possibility of aspirin-induced asthma by additives was also conceivable, it is unlikely that he is an aspirin-induced asthma patient because both aspirin and tolmetin inhalation tests were negative. Also, although acetaldehyde inhalation tests can give positive results in patients without alcohol-induced asthma as well as in patients with alcohol-induced asthma, Fujimura et al reported that alcohol-induced asthma patients have a selective bronchial hyperresponsivenessto acetaldehyde comparedto methacholine (6). The present patient also had a bronchial hyperresponsiveness to acetaldehyde.…”
Section: Discussionsupporting
confidence: 49%
“…Although a possibility of aspirin-induced asthma by additives was also conceivable, it is unlikely that he is an aspirin-induced asthma patient because both aspirin and tolmetin inhalation tests were negative. Also, although acetaldehyde inhalation tests can give positive results in patients without alcohol-induced asthma as well as in patients with alcohol-induced asthma, Fujimura et al reported that alcohol-induced asthma patients have a selective bronchial hyperresponsivenessto acetaldehyde comparedto methacholine (6). The present patient also had a bronchial hyperresponsiveness to acetaldehyde.…”
Section: Discussionsupporting
confidence: 49%
“…It should be noted that in these experiments, either in ATK- or in vehicle-treated mice, the Penh values were higher to those in the other experiments (Figure 5). This is likely due to the effect of ethanol, the ATK vehicle as this solvent has been shown to exacerbate airway constriction [18,19]. In spite of ethanol effect the results showed that pretreatment of mice with ATK markedly reduced LPS-induced airway constriction compared to ethanol-treated mice (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…that ethanol is not the substance causing the pulmonary response. Studies have shown that acetaldehyde, a direct metabolite of ethanol, causes pulmonary responses following inhalation (Fujimura et al, 1999), by increasing pressure at the airway opening (Myou et al, 1993); blood acetaldehyde was increased in patients suffering from alcohol-induced asthma with changes in FEV1 higher than 20%, but not in those with a response lower than 20%, while blood alcohol levels remained unchanged (Watanabe, 1991). Acetaldehyde has been detected in the expired air of human volunteers during and after a 6 h acute exposure to 25-1000 ppm ethanol (Tardif et al, 2004).…”
Section: Discussionmentioning
confidence: 97%